(untitled) (Research, Society and Development, 2020)
This article aims to reflect on self-ethics as a knowledge to reframe teaching. Through reflection, teaching knowledge can be problematized and reframed. Resignification is configured in the teacher’s creative process of assigning new meanings based on what is already known, giving a new meaning to the context in which it is inserted. Self-ethics understood as the ethics of reconnection is opposed to fragmented and disciplinary knowledge and requires a paradigmatic transition for the construction of the knowledge of religation. It deals with a a narrative review, based on books, articles and concepts used by Edgar Morin and other authors who seek to approach the theory of complexity of discussions about teaching knowledge.